Seasonal stratification of the estuarine macroinfauna of the Patos Lagoon estuary, southern Brazil - Rosa, Leonardo Cruz da (2006)
Stratified samples were seasonally collected to analyze the vertical distribution of the macroinfauna and sedimentological characteristics in a soft bottom estuarine habitat of the Patos Lagoon, southern Brazil. Physical-chemical characteristics of the sediments were quite similar among all sampling periods. Significant differences among strata were resulting of decrease of mean grain size and sorting coefficient and, an increase of fine sediment fractions at deeper layer. Highest macroinfauna densities were always observed in the surface sediments (0-5 cm of depth), with values varying from 63.5 to 90.3 % of the total collected organisms at summer and winter period, respectively. Among numerically dominant organisms, the pelecypod Erodona mactroides and the polychaete Nephtys fluviatilis were exclusively found at superficial strata (0-5 cm). Otherwise, the tanaid Kalliapseudes schubarti and the polychaetes Heteromastus similis and Laeonereis acuta, although distributed along all strata, display a clear preference for sub-superficial sediments (0-10 cm of depth). Temporal changes or vertical partitioning were not observed. The weak correlation with sedimentary characteristics suggests that macroinfauna stratification pattern has been probably related to biological factors such as feeding mode and/or body size of the species.